Bone mineral density and fracture risk in patients with type ii diabetes mellitus (review) - Sykal, Alexandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
The purpose of a literature review was to analyze the peculiarities of bone tissue organization in patients with diabetes mellitus (DM) II type by evaluating bone mineral density (BMD) and fracture risk. Review consists of three sections, which are the results of studies BMD and fracture risk in patients with type II diabetes, as well as pathogenesis of disorders in bone tissue in case of the said disease. During study of men and women with DM type II we revealed differences in BMD parameters in different segments of the skeleton. Most researchers have concluded that for DM type II BMD increased in the axial skeleton. There were positive correlation between body mass index and femoral neck BMD in women with DM type II. Potential factors affecting an increasing BMD in cases of DM type II include obesity, hyperinsulinemia, increased levels of androgens associated with obesity in women. However there are some works in which there were revealed no changes in BMD compared to healthy individuals or proven reducing of this parameter. On the one hand, the discrepancy of the indeces can be explained by population characteristics, on the other hand - the study was conducted in patients of different age and disease duration, and on different bone densitometers. Not in all cases they took into account comorbidities and features of the metabolic background of the organism. It was determined that gender features also appear on the BMD index. Either in the population or in patients with DM type II it was fixed lower skeletal mineralization in women comparing to men which one may explain by the increased risk of fracture in women. However despite on the high rates of BMD fracture risk in patients with DM type II is increased compared to healthy people indicating the need to consider other factors, for instance: risk of falls, microarchitecture and features of bone remodeling, etc.